2017
DOI: 10.1155/2017/1912724
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for Determining the Load Distribution of Single-Column Multibolt Connection

Abstract: The purpose of this research was to investigate the effect of geometric variables on the bolt load distributions of a cold-formed steel bolt connection. The study was conducted using an experimental test, finite element analysis, and an analytical method. The experimental study was performed using single-lap shear testing of a concentrically loaded bolt connection fabricated from G550 cold-formed steel. Finite element analysis with shell elements was used to model the cold-formed steel plate while solid elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results show that the proposed method is time efficient for the load distribution prediction of the bolted joint composite structures. Konkong and Phuvoravan [13] studied the influence of geometric variables on the load distribution of cold-formed steel bolt connections. The results of the parametric study showed that the t 2 /t 1 ratio controlled the efficiency of the bolt load distribution more than the other parameters studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the proposed method is time efficient for the load distribution prediction of the bolted joint composite structures. Konkong and Phuvoravan [13] studied the influence of geometric variables on the load distribution of cold-formed steel bolt connections. The results of the parametric study showed that the t 2 /t 1 ratio controlled the efficiency of the bolt load distribution more than the other parameters studied.…”
Section: Introductionmentioning
confidence: 99%